Challenges and Opportunities Brought by COVID-19 to the Education System: Based on Experience of China (Journal of Educational Sciences, 2021)
Covid-19 has widely spread and has affected all scope of activities in the world. Among the ac- tivities that faced challenges, includes education w\hich is undergoing radical changes such as online learning. This research sought to investigate the online education experience in the People’s Republic of China during the pandemic period. This research evaluated as well the disadvantages and advantages of online teaching, and presented better use of online education. Foreign and Chinese literatures have been reviewed and analyzed, compared and found out that Chinese experience of online education has achieved successful results, but in practice there were also challenges. The study’s conclusion suggests that it is necessary to upgrade the online education system and improve the methods of online teaching, to increase the number of teachers who are conversant with internet and who are techno savvy, to ensure the availability of technologies necessary for online learning, to expand the public’s understanding of online learning and finally to expand its capabilities.Key words: COVID-19, education, Chinese experience, offline learning, online learning, learning platforms.